Social insurance and allied services : memorandum on the Beveridge Report
1943-02-10 1943 1940s 24 pages 7. country's post-war obligations as a whole, and to that extent they may well have to give place to other objectives of social betterment which may be regarded as having a greater claim on the available resources of the country. III. DISTINCTION BETWEEN PAYMENTS FOR WANT AND IRRESPECTIVE OF WANT: (20) On its first objective of abolishing Want, the "Beveridge" Report refers to the results of certain Surveys made between 1928 and 1937, but it does not itself show how the agencies set up to deal with cases of Want - the Assistance Board and the Public Assistance Authorities - have failed to meet the situation. (21) We do not, of course, overlook the fact that those drawing Old Age Pensions and also the insured unemployed are in a more favourable position than other classes who may require assistance. These two classes can get their supplementary allowances from the Assistance Board where their needs are assessed on the basis of their own individual means and without their relatives being exposed to any claim for reimbursement, and the Old Age Pensioner can draw his Supplementary Allowance along with his ordinary Pension at the Post Office. As compared with that position, those drawing Health Insurance Benefit, Widows' Pensions or Workmen's Compensation, as also those who are uninsured, have to have recourse for any additional assistance to the Public Assistance Authority, where their needs are assessed, not on the basis of the applicant's own means, but on the basis of the income and means of the members of his household; and, if the applicant is unable to work, the Public Assistance Authority has power to claim, from parents and sons and daughters living outside the applicant's household, reimbursement of the Assistance granted. (22) These two Agencies - the Assistance Board and the Public Assistance Authorities - are therefore working under different rules, and it may well be that such real Want as does exist arises from the rules under which the respective tests of need are adjudicated and dealt with, or from the anomalies of procedure and administration which at present exist between these two Agencies. (23) So far as the Assistance Board is concerned, the London County Council in its evidence before the "Beveridge" Committee (Appendix G - page 208) made the following/ 200/B/3/2/C216/5/50